Functionalised POSS for materials science applications - Bent, Matthew (Trinity College (Dublin, Ireland). School of Chemistry, 2006)
The main aim of this work is to develop chemistry of POSS and related materials, which might have potential applications in nanotechnology. Chapter 1 of the thesis provides a general introduction into the area of POSS and related materials. Chapter 2 is dedicated to synthesis of different functionalised POSS. ... In the chapter 3 various reactions of halogen-, amino-, allyl- and cyclopentadienyl- functionalised POSS have been studied. ... In chapter 4 different trialkoxysilane derivatives such as (chloropropyl) triethoxysilane, (aminopropyl)triethoxysilane, allyltriethoxysilane have been used to functionalise Ti02 nanorods. ... In the chapter 5 preparation and effective purification techniques for multiwalled (MWNTs) nanotubes have been developed. ... Chapter 6 contains the experimental details of the procedures and techniques described in this thesis. Finally, chapter 7 presents conclusions and the future outlook for the research performed in this project.
Keywords: Chemistry, Ph.D.; Ph.D. Trinity College Dublin